2020
DOI: 10.1111/ncn3.12380
|View full text |Cite
|
Sign up to set email alerts
|

A case of area postrema syndrome associated with sick sinus syndrome in an elderly patient with neuromyelitis optica spectrum disorder: Case report

Abstract: Hiccups (singultus) are one of the most challenging symptoms to diagnose a cause. Causes range from the gastrointestinal and cardiovascular systems to the neurological system. 1 It is essential to remember that area postrema syndrome (APS), particularly in cases caused by neuromyelitis optica spectrum disorders (NMOSD), is an important differential diagnosis. 2 Persistent and intractable hiccups are a representative symptom in patients with NMOSD and associated with damage to areas abundant with the aquaporin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Only a few patients with NMOSD who presented with SSS due to medullary lesions have been reported. We have reviewed all previously reported NMOSD cases with SSS in a total of eight articles after searching PubMed and Medline [4][5][6][7][8][9][10][11]. Table 1 summarizes the eight previous reports of NMOSD patients with SSS and our report of two patients (patients no.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few patients with NMOSD who presented with SSS due to medullary lesions have been reported. We have reviewed all previously reported NMOSD cases with SSS in a total of eight articles after searching PubMed and Medline [4][5][6][7][8][9][10][11]. Table 1 summarizes the eight previous reports of NMOSD patients with SSS and our report of two patients (patients no.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few patients with NMOSD who presented with SSS due to medullary lesions have been reported. Table 1 summarizes the six previously reported NMOSD patients presenting SSS associated with medullary lesions, including our patient [ 4 – 8 ]. In our patient, frequent episodes of syncope were among the initial symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The patients reported by Tsouris and Okada et al [ 6 , 7 ] were admitted with a chief complaint of syncope, while syncope was noticed early after admission in the patients reported by Endo and Komaki et al [ 4 , 5 ]. Bigi et al [ 8 ] reported a young patient with area postrema involvement who displayed vomiting, hiccups, and sinus bradycardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation